Carbazoles on same main chain for polymer solar cells. Issue 5 (30th January 2013) - Qin, Ruiping; Jiang, Yurong; Ma, Heng; Yang, Le; Liu, Hengzhi; Chang, Fanggao
Abstract Planar conjugated 2, 7‐linked carbazole blocks: Q1(2, 7‐dibromo‐9‐octyl‐9H‐carbazole); Q2(7, 7′‐dibromo‐9, 9′‐dioctyl‐9H, 9′H‐2, 2′‐bicarbazole); Q3 (7‐bromo‐7′‐(7‐bromo‐9‐octyl‐9H‐carbazol‐2‐yl)‐9, 9′‐dioctyl‐9H, 9′H‐2, 2′‐bicarbazole) were coupled with same acceptor (4, 7‐di[2, 5‐thiophene]‐5, 6‐dioctyloxy‐2, 1, 3‐Benzothiadiazole) to prepare polymers HXS‐1, 2, 3 (Scheme 1). Bulk‐heterojunction polymer solar cells (BHJ PSCs) with these polymers were made. Power conversion efficiency of HXS‐1 was proved to be over 5.4%. It declined dramatically to 0.43% and 0.23% for HXS‐2 and 3 respectively. Their absorption and X‐ray diffraction pattern show the torsion angle in main chain increased when more carbazole units were added. More carbazoles will make polycondensation reaction more difficult to get high molecular weight polymers. The torsion angle was calculated using a semiempirical molecular orbital method. All the results pointed out that the coplanarity in the conjugated backbone was destroyed. Electron delocalization was disturbed because p‐orbital overlapping only occurs effectively in the parallel orbit so charge cannot move a longer distance. This study offers a useful and important insight to designing polymers for high performance PSCs. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013